Recommended data elements for health registries: a survey from a German funding initiative - Harkener, Sonja; Jenetzky, Ekkehart; Rupp, Rüdiger; Dell, Jennifer; Engel, Christoph; von Bargen, Maximilian Ferry; Finger, Robert P.; Glienke, Maximilian; Heinz, Carsten; Jersch, Patrick; Martin, David; Schmutzler, Rita; et al. (BMC medical informatics and decision making, 2024)
The selection of data elements is a decisive task within the development of a health registry. Having the right metadata is crucial for answering the particular research questions. Furthermore, the set of data elements determines the registries’ readiness of interoperability and data reusability to a major extent. Six health registries shared and published their metadata within a German funding initiative. As one step in the direction of a common set of data elements, a selection of those metadata was evaluated with regard to their appropriateness for a broader usage.
Gesehen am 30.09.2024